AGENCY CONFLICT AND EARNINGS MANAGEMENT - Pontoh, Winston; Budiarso, Novi Swandari (The Studies of Social Sciences, 2019)
This conflict between firm insiders and firm outsiders in case to allocate the free cash still unclear in the context of agency theory. This study examines the sample of 25 public firms in consumer goods industry listed in Indonesia Stock Exchange over period of 2010 until 2018 in term to detect agency conflict with earnings management as its application. This study finds that discretionary accruals as the proxy of earnings management is insignificant on debt policy and growth opportunities. Those findings indicate that, Indonesian public firms do not practicing earnings management which means agency conflict is not exist over the sample of this study.